X-linked cone dysfunction syndrome with myopia and protanopia. - Michaelides, M; Johnson, S; Bradshaw, K; Holder, G; Simunovic, M; Mollon, J; Moore, A; Hunt, D (2005)
PURPOSE: To perform a detailed clinical, psychophysical, and molecular assessment of members of 4 families with an unusual X-linked cone dysfunction syndrome associated with myopia. PARTICIPANTS: Affected and unaffected members of 4 British nonconsanguineous families. METHODS: Subjects underwent both detailed clinical examination and psychophysical testing. After informed consent was obtained, blood samples were taken for DNA extraction, and molecular genetic analysis was performed. The strategy for molecular analysis was to amplify the coding regions of the long and middle wavelength-sensitive cone opsin genes and the upstream locus control region by polymerase chain reaction and to examine these fragments for mutations by sequencing of DNA. RESULTS: The phenotype was almost identical in all 4 families, consisting of moderate to high myopia, astigmatism, moderately reduced acuity, and normal fundi. Electroretinography showed abnormal cone but normal rod responses. Psychophysical testing showed a selective impairment of long cones in combination with well-preserved middle cone and short cone function. There was no evidence to suggest that the phenotype was progressive. Molecular analysis of the X-linked opsin gene array in the 4 families indicated that affected males have inherited the same X-chromosome from their mother. In 2 families, a long/middle hybrid gene was detected. In a third family, the commonly described deleterious Cys203Arg amino acid substitution was identified in both the long and middle opsin genes. In the fourth family, the only abnormality was absence of a middle opsin exon 2; the cause of the protanopia in this family is uncertain. CONCLUSIONS: The X-linked cone dysfunction syndrome associated with myopia and dichromacy described here has many similarities to Bornholm eye disease, a condition previously mapped to Xq28. Except for the Cys203Arg substitution in one family, no alterations in the opsin gene array were identified that could underlie the cone dysfunction. It is therefore possible that the cone dysfunction may have a genetic origin different from that of the dichromacy.